Practical ethics for the food professionals ethics in research, education and the workplace - Clark, J. Peter, 1942-; Ritson, Christopher (IFT press series., 2013)
"This book offers a practical guide to the most pressing ethical issues faced by those working in food manufacturing and associated industries. Early chapters look at the fundamentals of ethical thinking and how lessons of medical ethics might be applied to the food industry. The book then addresses some issues specifically relevant to the food industry, including treatment of animals; the use of genetically modified organisms; food product advertising; health claims and sustainability. Several further chapters present case studies which show how ethical thinking can be applied in real life examples.This volume should be on the desk of every food industry professional responsible for important decisions about science, marketing, resources, sustainability, the environment and people"--